2015
DOI: 10.1016/j.thromres.2015.06.022
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS13 gene variants and function in women with preeclampsia: A population- based nested case- control study from the HUNT Study

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
1
2
1
1
Order By: Relevance
“…In accordance with our findings, several studies found statistically significant decreases in ADAMTS13 activity in preeclamptic women's serums over healthy controls [6,11,[13][14][15][16][17]. A few articles, however, found no significant differences between the two groups of individuals, suggesting that ADAMTS13 activity is not associated with PE [18][19][20]. Consequently, besides the strong correlation between significantly low levels of ADAMTS13 activity (below 10-20%) and TTP, a more average level cannot rule out preeclampsia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In accordance with our findings, several studies found statistically significant decreases in ADAMTS13 activity in preeclamptic women's serums over healthy controls [6,11,[13][14][15][16][17]. A few articles, however, found no significant differences between the two groups of individuals, suggesting that ADAMTS13 activity is not associated with PE [18][19][20]. Consequently, besides the strong correlation between significantly low levels of ADAMTS13 activity (below 10-20%) and TTP, a more average level cannot rule out preeclampsia.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, risk-factor variants were found in ADAMTD13, C3, and Complement Factor H (CFH) genes. It is worth noting that the study conducted by von Krogh et al did not find any correlation between the three investigated gene variants of ADAMTS13 and PE, including the rs28647808 variant, which our own study characterized as deleterious [20].…”
Section: Discussioncontrasting
confidence: 43%
“…In contrast, only a few papers reported no differences between the two groups, suggesting that ADAMTS13 activity is not significantly associated with PE [ 19 , 20 , 21 ]. In the study of Yoshida et al, pregnant women with HELLP syndrome were also included in the sample, but the sizes of the patient group ( n = 13) and the control group ( n = 128) are obviously inequivalent [ 20 ] Interestingly, according to von Krogh et al, no statistically significant differences were detected concerning lower levels, genotype, allele, and haplotype of the ADAMTS13 variants between the preeclamptic and the healthy control group of pregnant women [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The question is whether ADAMTS13 could be considered a reliable biomarker for the diagnosis of TTP, since there are several studies supporting a statistically significant decrease in ADAMTS13 in other TMAs, such as HELLP syndrome/preeclampsia [ 2 , 17 , 18 , 19 , 20 , 21 , 22 , 24 ]. ADAMTS13 activity values can vary from 12% to 43% in HELLP syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…не обнаружили каких-либо статистически значимых различий между физиологической беременностью и беременностью, осложненной ПЭ [51]. Также крайне противоречивы данные об активности ADAMTS-13 при ПЭ [51][52][53]. ADAMTS-13 разрушает vWF; однако недостаток металлопротеиназы у женщин с ПЭ может привести к непоправимым последствиям.…”
Section: особенности функционирования Adamts-13 и фактора фон виллебр...unclassified